DIVERSITY, ETHNIC POLITICS, AND POLICY FORMULATION IN LEGISLATIVE INSTITUTIONS: KEBERAGAMAN, POLITIK ETNIS, DAN FORMULASI KEBIJAKAN DI LEMBAGA LEGISLATIF - Ahmad, Jafar; Wafi, Mahmud Hibatul; Wahdini, Muhammad (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research discusses how ethnic diversity in the city of Sungai Penuh, Jambi, influences the legislative body in playing its political role. Through a case study approach, this research emphasizes the interaction patterns of legislative actors in the legislative process based on ethnic relations, and it conducts interviews to generate descriptive data to reveal the cultural diversity of ethnic groups and the political expression of the legislative institution in Sungai Penuh. The research findings indicate the presence of ethnic diversity in Sungai Penuh, including the Kerinci people (79.73%), Minang (15.73%), Javanese (2.13%), Malay (0.27%), Batak (0.27%), Chinese (0.13%), and Banjar (0.07%). In addition to the Kerinci ethnic group, which is the majority, other ethnic groups are also involved in the legislative institution, such as the Minang, Javanese, and Batak. The election of Regional House of Representatives (DPRD) members from different ethnicities in Sungai Penuh is driven by the support of the same ethnic group as the dominant voters (instrumentalist approach), as well as their significant role in the community. This affects the implementation of priority programs by DPRD, which tends to accommodate the interests of their constituents. Nevertheless, the combination of dominant and minority ethnic groups provides a variety of ideas and approaches in the dynamics of ethnic politics among legislative members.